Safety and Efficacy of the 10-Day Melarsoprol Schedule for the Treatment of Second Stage Rhodesiense Sleeping Sickness - Kuepfer, Irene; Schmid, Caecilia; Allan, Mpairwe; Edielu, Andrew; Haary, Emma P.; Kakembo, Abbas; Kibona, Stafford; Blum, Johannes; Burri, Christian (PLoS Neglected Tropical Diseases, 2012)
Objective: Assessment of the safety and efficacy of a 10-day melarsoprol schedule in second stage T.b. rhodesiense patients and the effect of suramin-pretreatment on the incidence of encephalopathic syndrome (ES) during melarsoprol therapy. Design: Sequential conduct of a proof-of-concept trial (n = 60) and a utilization study (n = 78) using historic controls as comparator. Setting: Two trial centres in the T.b. rhodesiense endemic regions of Tanzania and Uganda. Participants: Consenting patients with confirmed second stage disease and a minimum age of 6 years were eligible for participation. Unconscious and pregnant patients were excluded. Main Outcome Measures: The primary outcome measures were safety and efficacy at end of treatment. The secondary outcome measure was efficacy during follow-up after 3, 6 and 12 months. Results: The incidence of ES in the trial population was 11.2% (CI 5–17%) and 13% (CI 9–17%) in the historic data. The respective case fatality rates were 8.4% (CI 3–13.8%) and 9.3% (CI 6–12.6%). All patients discharged alive were free of parasites at end of treatment. Twelve months after discharge, 96% of patients were clinically cured. The mean hospitalization time was reduced from 29 to 13 days (p,0.0001) per patient. Conclusions: The 10-day melarsoprol schedule does not expose patients to a higher risk of ES or death than does treatment according to national schedules in current use. The efficacy of the 10-day melarsoprol schedule was highly satisfactory. No benefit could be attributed to the suramin pre-treatment.
Keywords: Melarsoprol Schedule; Treatment; Rhodesiense Sleeping Sickness